1875 Pa. Laws 48, no. 52, § 1 - (:unkn) unknown (My University, 1875)
That it shall not be lawful for any person or persons to erect, place or have any booth, stall, tent, carriage, boat, vessel, or any other place whatever, for the purpose of selling, giving, or otherwise disposing of any spirituous, vinous or malt liquors, or cider, or any fermented liquors whatsoever, or any admixtures thereof, or any liquid compounded or composed, in whole or part, of alcohol, or any other intoxicating drink whatever, (except as hereinafter excepted,) within three miles of the place of holding any soldiers' encampment or re-union in this state, during the time of holding such encampment or re-union."
Keywords: ARMED FORCES